Impact of seed vigor and water stress on the early growth and survival of falcata (Falcataria Falcata (L.) Greuter & R. Rankin) seedlings (Bangladesh Journal of Botany, 2025)
The impact of seed vigor and water stress on the early growth and survival of Falcataria falcata (L.) Greuter & R. Rankin seedlings were thoroughly investigated. A total of one hundred seedlings were subjected to a growth test in a 2 × 5 factorial experiment following a Completely Randomized Design (CRD). The results revealed significant differences (p < 0.01) in mean height, leaf number, leaf area, and % survival across the various treatments. It was observed that T1 and T6, which received daily watering, exhibited the highest mean height, measuring 5.6 and 5.2 cm, respectively. T1 and T6 also displayed significantly higher mean leaf numbers, with 14 and 13 leaves, respectively, and more significant mean leaf areas of 184.30 mm2 and 181.45 mm2. Furthermore, the % survival rate remained at 100% after five weeks for treatments T1, T2, T6, and T7. Notably, seed vigor and its interaction with watering frequency did not significantly impact the previously mentioned parameters. The study recommends a daily watering frequency of 10 ml for optimal growth of F. falcata.Bangladesh J. Bot. 54(1): 1-6, 2025 (March)